Pengaruh Senam Kaki Diabetik terhadap Neuropati pada Pasien Diabetes Melitus - Lutfia Qurotulnguyun; Fidha Rahmayani; Sutarto (CV. Jasa Sukses Abadi, 2023)
The prevalence of people with diabetes mellitus has increased every year. Indonesia is ranked 7th in the world with 10.7 million people with diabetes. Diabetes in the long term can cause macrovascular and microvascular complications. One of the main complication of diabetes mellitus is diabetic neuropathy. Diabetic neuropathy is a microvascular complication that causes peripheral nerve dysfunction, which attacks the lower extremities, especially the legs. About 50% people with diabetes mellitus experience diabetic neuropathy. If not treated properly, this condition can reduce the patient's quality of life, increase the risk of amputation, and even death. Drugs are often the main choice for therapy, but cost constraints and side effects cause interest to look for other treatment alternatives. Treatment that can be done is to exercise. One of the recommended sports is diabetic foot exercise. Diabetic foot exercise is a light exercise focused on the legs consisting of ten steps. This sport can be done easily, does not cost money, and does not take a long time. Several studies state that diabetic foot exercises can be an alternative to prevent and inhibit the worsening of neuropathy in patients with diabetes mellitus by helping to accelerate peripheral blood circulation and strengthen muscles in the lower extremities to prevent injuries and foot deformities.